2016
DOI: 10.1016/j.bbmt.2015.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Haploidentical Natural Killer Cell Infusion for Treatment of Relapsed or Persistent Myeloid Malignancies Following Allogeneic Hematopoietic Cell Transplantation

Abstract: We conducted a phase 2 study to determine the efficacy of HLA-haploidentical related donor NK cells following cyclophosphamide based lymphodepletion in patients with relapsed or progressive acute myelogenous leukemia (AML) or myelodysplastic syndrome (MDS) following allogeneic HCT. Eight patients (2 with MDS, 6 with AML) were treated with cyclophosphamide 50 mg/kg on day −3 and day −2 prior to infusion of NK cells isolated from a haploidentical related donor. One person additionally received fludarabine 25 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 36 publications
1
100
1
Order By: Relevance
“…In a small study in AML patients with impending relapse, Uharek et al showed favorable two-year survival (40% vs. 11%) when treated with a haploidentical transplantation in combination with post-transplant NK cell infusion, as compared to haploidentical transplantation alone. Also in multiple myeloma patients, NK cell were infused after both autologous and allogeneic transplantation [37,38] with no safety concerns.…”
Section: Post-transplantation Nk Cell Therapymentioning
confidence: 99%
“…In a small study in AML patients with impending relapse, Uharek et al showed favorable two-year survival (40% vs. 11%) when treated with a haploidentical transplantation in combination with post-transplant NK cell infusion, as compared to haploidentical transplantation alone. Also in multiple myeloma patients, NK cell were infused after both autologous and allogeneic transplantation [37,38] with no safety concerns.…”
Section: Post-transplantation Nk Cell Therapymentioning
confidence: 99%
“…As the impact of KIR-ligand mismatch in the transplant setting became evident, the focus of the trials shifted toward the use of allogeneic NK cells either in combination with HSCT or in a non-HSCT setting (Table 3). 71,[141][142][143][144] Allogeneic NK cells are less likely to be subject to the inhibitory response resulting from NK cell recognition of self-MHC molecules, as seen with autologous NK cells. Moreover, several studies have shown that infusion of haploidentical NK cells to exploit the missing-self concept is safe and can mediate impressive clinical activity in some patients with AML.…”
Section: Nk Cell Adoptive Immunotherapymentioning
confidence: 99%
“…71,[130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] Results of the initial trials using ex vivo activated autologous NK cells were mostly unsatisfactory, [130][131][132][133][134][135][136][137][138] likely because of the inhibition of autologous NK cells by self-HLA molecules. As the impact of KIR-ligand mismatch in the transplant setting became evident, the focus of the trials shifted toward the use of allogeneic NK cells either in combination with HSCT or in a non-HSCT setting (Table 3).…”
Section: Nk Cell Adoptive Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Haploidentical NK cells are also being investigated for relapsed/refractory AML (RR-AML). Eight patients with AML or MDS following prior alloSCT received lymphodepletion followed by donor NK cell infusion and IL-2 [28]. Although one patient experienced remission, no survival benefit was observed and no donor NK cells were detected in patients.…”
Section: Natural Killer Cell Therapymentioning
confidence: 99%